Bose-Einstein Condensation in Financial Systems - Staliūnas, K. (Nonlinear Analysis: Modelling and Control, 2005)
We describe financial systems as condensates, similar to Bose-Einstein condensates, and calculate equilibrium statistical distributions following from the model. The calculated distribution of investments into speculated financial asset is exponentially truncated Pareto distribution, and the calculated distribution of the price moves is exponentially truncated Levy distribution. The calculated from the model distributions correspond well to the empirically observed distributions.
Keywords: econophysics; Non-Gaussian distributions; Levy distributions; Bose-Einstein statistics